2021
DOI: 10.1111/1744-7917.12935
|View full text |Cite
|
Sign up to set email alerts
|

A venom protein of ectoparasitoid Pachycrepoideus vindemiae, PvG6PDH, contributes to parasitism by inhibiting host glucose‐6‐phosphate metabolism

Abstract: To achieve successful development, female parasitoids, while laying eggs, introduce various virulence factors, mainly venoms, into host insects to manipulate their physiology. Although numerous studies have been conducted to characterize the components of venoms that regulate host immune responses, few systematic investigations have been conducted on the roles of venom proteins in host metabolic regulation. In this investigation, we characterized a novel venom protein in Pachycrepoideus vindemiae called glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(47 reference statements)
2
5
0
Order By: Relevance
“…Moreover, Zhou et al (2021) screened 278 carbohydrate digestion-related genes differently expressed upon 24 h and 48 wasp parasitization based on transcriptome analysis, which was in good accordance with our present study. In a recent investigation, we reported that the glucose-6-phosphate metabolism of host Drosophila was inhibited after 24 h and 48 h Pachycrepoideus vindemiae parasitization [ 46 ], broadly supporting our present work that most metabolism-related DEGs were significantly downregulated at 24 h and 48 h post-parasitization. To further validate the expression levels of metabolism-related DEGs in parasitized FAW and to contrast with the unparasitized host, 20 genes were randomly selected for qPCR verification, which well correlated with the data of RNA-seq for quantifying the transcriptional levels of these DEGs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, Zhou et al (2021) screened 278 carbohydrate digestion-related genes differently expressed upon 24 h and 48 wasp parasitization based on transcriptome analysis, which was in good accordance with our present study. In a recent investigation, we reported that the glucose-6-phosphate metabolism of host Drosophila was inhibited after 24 h and 48 h Pachycrepoideus vindemiae parasitization [ 46 ], broadly supporting our present work that most metabolism-related DEGs were significantly downregulated at 24 h and 48 h post-parasitization. To further validate the expression levels of metabolism-related DEGs in parasitized FAW and to contrast with the unparasitized host, 20 genes were randomly selected for qPCR verification, which well correlated with the data of RNA-seq for quantifying the transcriptional levels of these DEGs.…”
Section: Discussionsupporting
confidence: 91%
“…In one relevant example, the host polysaccharides were hydrolyzed upon P. puparum parasitism to obtain energy for the development of parasitoid offspring [ 15 ]. Similarly, it was further demonstrated that P. vindemiae has a vital role in regulating host glucose metabolism [ 46 ]. These cases provided a possible explanation for the enrichment of purine pentose, glutathione, and other metabolism-related DEGs in KEGG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The wasp enzyme causes transcriptional inhibition of D. melanogaster G6PDH, leading to increased G6P levels in the host, which can be used as a substrate for wasp development. In RNAi-treated wasps, a lower infectivity capacity is observed when compared to control insects, supporting the idea of immunometabolic interactions involving PPP enzymes ( Yang et al, 2022 ). The findings discussed thus far highlight the promising potential of targeting the immune system and metabolic pathways, particularly PPP, for the development of novel strategies to control arthropods.…”
Section: Immunometabolic Aspects Of Pentose Phosphate Pathwaysupporting
confidence: 57%
“…Our results suggest that the expression of these genes changes to varying degrees after knocking down SlFAS1 , indicating that these genes may be connected with SlFAS1 to jointly regulate the synthesis of lipids in the body. Yang et al [ 38 ] revealed that the glucose-6-phosphate (G6P) metabolism of the host D. melanogaster parasitized by Pachycrepoideus vindemmiae is affected by PvG6PDH ; the expression levels of the host G6P-metabolism-related genes changed at different time points after the host was injected with PvG6PDH , suggesting the expression of nutrition–related genes can be affected by other genes. In a recent study, Wang et al [ 13 ] also reported that silencing GpylFAS1 affected the expressions of the other fatty acid synthesis-related genes in G. pyloalis .…”
Section: Discussionmentioning
confidence: 99%